PARTICLE SIZE DISTRIBUTIONS OF CLAY-RICH SEDIMENTS AND PURE CLAY MINERALS: A COMPARISON OF GRAIN SIZE ANALYSIS WITH SEDIMENTATION FIELD-FLOW FRACTIONATION - Hassellov M.; Lyven B.; Bengtsson H.; Jansen R.; Turner D.R.; Beckett R. (My University, 2001)
Two clay-rich coastal sediment samples have been characterised together with three pure clays identified as major components of the sediment samples. The mineralogy of the sediments was determined by X-ray diffraction, and their bulk properties measured (organic carbon content, leachable iron and manganese, surface area and cation exchange capacity). A simple approach is used to model the properties of the sediments from those of their pure clay components. Good agreement is found for cation exchange capacity and specific surface area indicating that the clay minerals are the most important constituents influencing the sediments' surface properties. Particle size distributions were assessed by conventional grain size analysis, and also by Sedimentation Field-Flow Fractionation (SedFFF). These two approaches yield sharply differing size distributions; in particular, conventional grain size analysis indicates a much greater proportion of submicron particles. Similar results are obtained from analysis of pure clays. The most likely reason for this is artifacts introduced in the unavoidable 1 μm prefractionation used for SedFFF.
Keywords: SEDIMENT; SIZE DISTRIBUTION; FIELD-FLOW FRACTIONATION; XRD; CLAY MINERALOGY; SPECIFIC SURFACE AREA; CATION EXCHANGE CAPACITY